The role of flavin mononucleotide (FMN) as a potentially clinically relevant biomarker to predict the quality of kidney grafts during hypothermic (oxygenated) machine perfusion - van de Leemkolk, FEM; Lo Faro, ML; Shaheed, S; Mulvey, JF; Huurman, VAL; Alwayn, IPJ; Putter, H; Jochmans, I; Lindeman, JHN; Ploeg, RJ (Public Library of Science, 2023)
Hypothermic machine perfusion (HMP) provides preservation superior to cold storage and may allow for organ assessment prior to transplantation. Since flavin mononucleotide (FMN) in perfusate has been proposed as a biomarker of organ quality during HMP of donor livers, the aim of this study was to validate FMN as a biomarker for organ quality in the context of HMP preserved kidneys. Perfusate samples (n = 422) from the paired randomised controlled COPE-COMPARE-trial, comparing HMP with oxygenation (HMPO2) versus standard HMP in kidneys, were used. Fluorescence intensity (FI) was assessed using fluorescence spectroscopy (excitation 450nm; emission 500-600nm) and validated by fluorospectrophotometer and targeted liquid chromatography mass spectrometry (LC-MS/MS). Fluorescence intensity (FI)(ex450;em500-600) increased over time during machine perfusion in both groups (p<0.0001). This increase was similar for both groups (p = 0.83). No correlation, however, was found between FI(ex450;em500-600) and post-transplant outcomes, including day 5 or 7 serum creatinine (p = 0.11; p = 0.16), immediate graft function (p = 0.91), creatinine clearance and biopsy-proven rejection at one year (p = 0.14; p = 0.59). LC-MS/MS validation experiments of samples detected FMN in only one perfusate sample, whilst the majority of samples with the highest fluorescence (n = 37/38, 97.4%) remained negative. In the context of clinical kidney HMP, fluorescence spectroscopy unfortunately appears to be not specific and probably unsuitable for FMN. This study shows that FMN does not classify as a clinically relevant predictive biomarker of kidney graft function after transplantation.